Two case reports of malignant melanoma rectum - Sathyan, Jeena K.; Kamat, Manmohan; Sharma, Varsha; Shetye, Shravani; Barman, Seema (International Surgery Journal, 2021)
Malignant melanoma of the rectum is an extremely rare disease. It typically presents in the fifth or sixth decade predominantly in female sex. The first symptoms are nonspecific such as bleeding, anal mass or pain. A timely diagnosis of melanoma is made even more difficult due to lack of obvious pigmentation and histologically amelanotic. Anorectal malignant melanoma spread along submucosal planes and are often beyond complete resection at the time of diagnosis. Prognosis is very poor. We present a rare case of malignant melanoma of rectum in a 21-year-old male, who was diagnosed at advanced stage, and a case of malignant melanoma in a 50-year-old male, who underwent abdominoperineal resection with permanent colostomy. Anorectal malignant melanoma is difficult to diagnose and prognosis is poor.